The genus Scoparia (Lepidoptera, Crambidae) from Galongla Snow Mountain of China, with DNA barcoding and descriptions of three new species. Issue 3 (3rd May 2016) - Li, Weichun; Jie, Lulan; Liu, Dong
Abstract : Four species from Galongla Snow Mountain, southeastern Tibet of China are revealed as members of the genus Scoparia by combining DNA barcoding (658 bp of the mitochondrial gene cytochrome c oxidase subunit I, COI ) and morphological characters. Three species are described as new to science: S. varians Li, sp. nov., S. nussi Li, sp. nov. and S. lii Li, sp. nov. The female of S. simplicissima Li is described for the first time. All species are described and illustrated, including the habitat, characters of intraspecific variability and sexual dimorphism. A map showing the localities on the Tibetan Plateau, where more than 40% of Chinese Scoparia species are endemic, is also provided. The results suggest the genus Scoparia has high species diversity on the Tibetan Plateau and may exhibit potential for specific adaptation to high plateau environments.